Open Source Verification under a Cloud - Breuer, Peter; Pickin, Simon (Electronic Communications of the EASST, 2010)
An experiment in providing volunteer cloud computing support for automated audits of open source code is described here, along with the supporting theory. Certification and the distributed and piecewise nature of the underlying verification computation are among the areas formalised in the theory part. The eventual aim of this research is to provide a means for open source developers who seek formally backed certification for their project to run fully automated analyses on their own source code. In order to ensure that the results are not tampered with, the computation is anonymized and shared with an ad-hoc network of volunteer CPUs for incremental completion. Each individual computation is repeated many times at different sites, and sufficient accounting data is generated to allow each computation to be refuted.